2021
DOI: 10.1002/agj2.20532
|View full text |Cite
|
Sign up to set email alerts
|

A regional analysis model of maize kernel moisture

Abstract: With the popularization of late-maturing and high-yielding maize (Zea mays L.) hybrids, high kernel moisture concentration at the usual harvest time has resulted in increased kernel breakage and additional drying costs. To achieve low kernel moisture at harvest in China's maize-growing areas, there is a need for the selection of fast dry-down hybrids and the prediction of the ideal harvest time. During 2014-2017, the time-series kernel moisture concentrations of three maize hybrids were measured in the field i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…However, there is no clear quantitative relationship between the environment factors and grain drying process (Borrás & Westgate, 2006; Hallauer & Russell, 1961). Therefore, we used a simplified model for the AcT after silking to fit the changes of GMC, and some previous studies have demonstrated that this method can meet our research needs (Li, Ming, et al., 2018a; Li, Ming, Gao, et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no clear quantitative relationship between the environment factors and grain drying process (Borrás & Westgate, 2006; Hallauer & Russell, 1961). Therefore, we used a simplified model for the AcT after silking to fit the changes of GMC, and some previous studies have demonstrated that this method can meet our research needs (Li, Ming, et al., 2018a; Li, Ming, Gao, et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Maize ears, which are independent reproductive organs, consist of kernels, husks, cobs, and peduncles. The kernels are the portion with direct economic value, and the kernel growth, development, water dynamics, and influencing factors have therefore been extensively studied [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%